Adjustment of TV viewing: Adolescents in relation to their family structure - Tomar, Sanjeev (Bodhi: An Interdisciplinary Journal, 2013)
Bodhi: An Interdisciplinary Journal, 5, 2011, Page 160-172 DOI: http://dx.doi.org/10.3126/bodhi.v5i1.8051